The Influence of Leadership Style and Cognitive Attitudes on Patient Safety Culture With Coordination as a Moderation Variable in Inpatient Nurses at Tzu Chi Hospital - Suwoto Suwoto; Rina Mutiara; Rita Kemala (STIKES Columbia Asia Medan, 2024)
This research is based on the results of initial observations which indicate that several safety incident problems will occur in the year 2022. The aim of this research is to reveal empirically the influence of leadership style and cognitive attitudes on patient safety culture with coordination as a moderator. This type of research is quantitative with a cross sectional study design. The population used is nurses who work in inpatient installations. The sampling technique is non-probability sampling, with perm = calculation of the number of samples using Slovin's formula with an error rate of 10%, so that a total sample of 64 respondents was found. The data collection technique uses a questionnaire, and the analysis method uses three box method analysis and PLS-SEM with the help of the Smart-PLS program. The results of the analysis prove that leadership style, cognitive attitude and coordination simultaneously and partially influence patient safety culture, and cognitive attitude is the most dominant variable capable of improving patient safety culture. Coordination cannot moderate the influence of leadership style on patient safety culture, but coordination can weaken the influence of cognitive attitudes on patient safety culture.